Pemenuhan Hak Upah Pekerja pada CV. Persada Sejahtera Ponorogo - Fachriza M. M, Muhammad; Egista H. P, Radhya (Media of Law and Sharia, 2025)
The research explores the fulfillment of workers' wage rights, with a particular focus on whether these rights support a decent and prosperous standard of living. The main objective is to examine how CV. Persada Sejahtera in Ponorogo Regency fulfills its wage obligations to employees and whether this fulfillment complies with Law Number 6 of 2023. An empirical approach was employed, involving both a review of relevant legal regulations and the collection of data through real-world observations. Data were gathered via interviews with workers, employers, and representatives from the Department of Manpower and Transmigration in Ponorogo Regency, as well as through a literature review. The findings indicate that the fulfillment of workers' wage rights at CV. Persada Sejahtera remains suboptimal. Several rights—particularly those related to the minimum wage—are not being met in accordance with prevailing legal standards. The study also identifies factors contributing to this non-compliance, which include internal elements (such as worker and employer dynamics) and external influences (such as the role of the Department of Manpower and Transmigration)